PENYELESAIAN PERKARA KONEKSITAS TENTANG TINDAK PIDANA PENGANIAYAAN OLEH ANGGOTA TNI DAN MASYARAKAT SIPIL (ANALISIS PUTUSAN NO 189-K/PM. II-08/AL/IX/2024) - Akbar Kuntara; Sujono (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
Connectivity is a criminal matter that has distinctive characteristics because it involves perpetrators from two different jurisdictions, namely civil and military. Connectivity refers to the consolidation of investigations into related criminal cases to be examined and decided jointly in a single court. In legal enforcement practice, particularly in criminal cases involving both military and civil elements, fragmentation of authority often leads to disparities in sentencing. This study aims to analyze the resolution of connectivity cases based on Decision Number 189-K/PM.I I-08/AL/IX/2024 in a criminal case of assault involving members of the Indonesian National Armed Forces (TNI) and civilians, which includes a discussion of connectivity cases according to connectivity procedural law and a legal analysis of the court decision. The method used is normative legal analysis, referencing legislative regulations, legal doctrine, and court decision analysis. The research findings indicate that although the mechanism of joint trial has been regulated in the Criminal Procedure Code (KUHAP) and Law No. 31 of 1997 on Military Courts, its implementation in practice has not been fully realized. The division of case handling between the general and military courts can lead to an imbalance in the application of legal sanctions and reduce the application of the principle of substantive justice.